The childhood in the Homeric poems - Pinto, Ana Paula (Romanitas - Revista de Estudos Grecolatinos, 2020)
As the first European literary documents, the Iliad and the Odyssey ensure in the cultural history of the West a unique status: assuming itself since Antiquity as the first foundation of philological and philosophical research, and superior literary and artistic model, and today tended to be interpreted in the framework of slow creative elaboration of generations of aedos, based on a peculiar technique of production and transmission, both articulate in an enigmatic poetic plot, from their traditional nature, threads of mythic narratives and historical realities that modern archaeological investigations confirm. Starting from the poetic pretext offered by the two works, we propose to trace references to the universe of childhood. Some, generic, occur as images of a certain extract from human society, marked by peculiar characteristics, functions and needs. Others, supported by specific mentions of determined children, assume a specific dramatic functionality in the mythical plot of the two poems, which contributes to the peculiar symbolic density of the narrative.
Keywords: Homer; Iliad; Odyssey; Childhood; Aedos